Development of Wireless Control System for Smart Street Lighting using ESP8266 - Fuada, Syifaul; Adiono, Trio; Siregar, Lindawani (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In this paper, we report a smart street lighting control system using the ESP8266 which is a low-cost Wi-Fi chip with full TCP/IP stack and microcontroller capability. Our system is equipped with a web server developed in HTML code. Hence, our smart street lighting system can be controlled wirelessly to turn ON or turn OFF, and it can be monitored its environmental condition (i.e., temperature and humidity around the system). All sensors used in this system are pure digitally-outputted sensor: DHT11 to monitor the ambient temperature and humidity and BH1750 to adjust the street light intensity automatically. The dimming technique was applied in the control system by using Pulse Width Modulation (PWM). The system was divided into two main parts: Gateway and Node in which these two parts employ the ESP8266. The Gateway as a coordinator will send a message to the node as an end device (in this work, the streetlight act as a Node). Later, the node will send the ACK to the Gateway. As results, each node can send a message to other nodes.